THE ROLE OF HOMEROOM TEACHERS ON THE DISCIPLINE OF CLASS V STUDENTS MIS MARDLIYATUL - Alia Putri, Tita Diah; Siregar, Romaito; Sabrina, Chailla; Hanifah Tamba, Eti; Amirul, Bani (Faculty of Tarbiyah nad Teacher Training, 2024)
This study aims to examine the role of homeroom teachers in improving the discipline of grade V students at MIS Mardliyatul. Discipline is an important aspect of education that directly affects the teaching and learning process and students' academic achievement. Homeroom teachers are responsible for monitoring, guiding, and implementing discipline rules in the classroom. This research used a qualitative method with a case study approach, involving direct observation, in-depth interviews with homeroom teachers, teachers, and students, and analysis of related documentation. The results showed that homeroom teachers play a strategic role in shaping student discipline through personalized approaches, consistent application of rules, and effective communication with students and parents. In conclusion, the active role of homeroom teachers is essential in creating a disciplined learning environment conducive to students' academic and character development.